(untitled) (World Science, 2022)
The aim of our research is to introduce new innovative training courses in theprogram of physical medicine and rehabilitation, taking into account the results of statistical analysis of survey data among students andundergraduates of the Faculty of Physical Medicine and Rehabilitation of the University of Sports. 230 students, 48 graduates and 6 employers were interviewed. Based on the analysis of the obtained results, we consider it expedient to add the following teaching courses to the program of medicine and rehabilitation: ″Modern Technologies in Motion Biomechanics″, ″Biotechnological Basis of Rehabilitation″ and ″Psychosocial Rehabilitation″. The first one will teach students how to use sensor and video-computer technologies for qualitative and quantitative movement analysis, the second one will furnish the students with recent insights into the biotechnological basis of rehabilitation and the third one will teach students how to work with people having mental disabilities.